ANALISIS PENGARUH MODAL USAHA DAN BIAYA PRODUKSI TERHADAP HASIL PRODUKSI TEMBAKAU DI KECAMATAN JEROWARU KABUPATEN LOMBOK TIMUR PADA MASA PANDEMI COVID-19 - Rendi Wahyudi (Fakultas Ekonomi Universitas Islam Al-Azhar, 2021)
The purpose of this study is to determine and analyse the effect of business capital and production costs on tobacco production in Jerowaru District, East Lombok Regency during the pandemic Covid-19. This research uses a quantitative approach. The data collection technique uses in-depth interviews based on questionnaires. Data analysis using multiple linear regression, which consists of two independent variables and one dependent variable, namely the variable business capital (X1), production costs (X2), and production yield (Y). The findings of this study indicate that partially the capital (X1) value of t count 4,850> t table 4,303 means that business capital (X1) has a significant effect on the production of tobacco farmers in Jerowaru District, East Lombok Regency since 2014 to 2020, while production costs (X2) t value -2.152 <t table 4.303 means that production costs do not have a significant effect on the production yield (Y) of tobacco farmers in Jerowaru District, East Lombok Regency from 2014 to2020.